The Role of BAWASLU of North Sumatra in Enforcing Administrative Compliance of the 2024 Election for Candidates of the Regional House of Representatives of North Sumatra - Harahap, Taufiq Ismail; Harahap, Herlina Hanum (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze the role of the North Sumatra Provincial Election Supervisory Agency (Bawaslu) in enforcing administrative compliance in the 2024 elections, particularly with regard to legislative candidates for the North Sumatra Regional Representative Council (DPRD). Administrative compliance is a crucial aspect in ensuring the integrity and transparency of the electoral process. This study uses a descriptive qualitative approach with data collection methods through documentation studies, in-depth interviews, and participatory observation. The results show that Bawaslu North Sumatra carries out its supervisory role through three main functions: prevention, enforcement, and education. Despite various strategic measures such as the dissemination of regulations and the issuance of advisory letters, various forms of administrative violations were still found, such as delays in uploading documents or data discrepancies in the candidate information system (SILON). Factors hindering Bawaslu's performance include limited human resources and weak administrative sanctions. This study recommends improving coordination between election institutions and strengthening Bawaslu's regulations and oversight capacity at the provincial level.